1990
DOI: 10.1107/s0108270190005492
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of the structure of bi(9,10-dihydro-9,10-anthracenediyl) at 198 K

Abstract: Abstract. C28H20, M, = 356.4, orthorhombic, Pbca, a = 8.101 (1), b = 12.034 (2), c = 18.753 (6) A, V= 1828.1 (7)A 3, Z = 4 (the asymmetric unit is half a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
2
5
0
Order By: Relevance
“…that it consists of a central prismatic core from which four pyridine rings extend. We believe that this is the first structurally characterized coordination compound to possess this arrangement, which bears a close resemblance to the well known face-to-face 9,9% 10,10'-bridged photodimers of anthracene (Abboud et al, 1990) and related organic molecules (Ando et al, 1995). Furthermore, the fact that the Agl...AglA [2.9954 (3) ,4,] separation is considerably shorter than the S1...S1A [5.086(1)A] distance produces a distortion to this general topology that has been observed in a transannularly-bridged derivative of an anthracene dimer (Herges et al, 1994).…”
Section: Commentsupporting
confidence: 60%
“…that it consists of a central prismatic core from which four pyridine rings extend. We believe that this is the first structurally characterized coordination compound to possess this arrangement, which bears a close resemblance to the well known face-to-face 9,9% 10,10'-bridged photodimers of anthracene (Abboud et al, 1990) and related organic molecules (Ando et al, 1995). Furthermore, the fact that the Agl...AglA [2.9954 (3) ,4,] separation is considerably shorter than the S1...S1A [5.086(1)A] distance produces a distortion to this general topology that has been observed in a transannularly-bridged derivative of an anthracene dimer (Herges et al, 1994).…”
Section: Commentsupporting
confidence: 60%
“… The proposed structure of the product, the so called dianthracene ( 2 ) was confirmed through X-ray analysis by Ehrenberg one century later . The most remarkable structural feature of dianthracene is the rather long C–C bond of 1.62 Å between the bridgehead carbon atoms. …”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of 4 has been refined by Choi and Marinkas 11 at room temperature and by Abboud et al 12 at 198 K. They have shown that its two bridge bonds connecting the two anthracene components are 1.624 11 and 1.618(3) 12 Å, respectively. MNDO calculations 13 underestimate this long single bond by 0.04 Å.…”
mentioning
confidence: 99%